IDENTIFIKASI JENIS TUMBUHAN HUTAN YANG DIGUNAKAN SEBAGAI PENGOBATAN TRADISIONAL OLEH MASYARAKAT KECAMATAN BALLA KABUPATEN MAMASA - Faradilah Farid Karim; Yunitya, Yunitya; Demmangapi’ B, Elvis; Srimuliadi, Srimuliadi; D, Reskianto; Sanda Limbong, Apni (Forestry Study Program University Of Mataram, 2024)
One of the areas in Indonesia that still maintains the culture and tradition of traditional medicine is Balla District, Mamasa Regency, West Sulawesi Province. The use of forest plants as traditional medicine by the community has been going for a long time and is supported by abundant natural resources. The purpose of this study was to identify the types of forest plants used by the community in traditional medicine along with plant parts, how to process them and how to use them. This type of research is descriptive qualitative with a survey method with field observations, semi-structured interviews and literature studies. The selection of informants was carried out by snowball sampling. Data analysis used a qualitative descriptive approach presented in the form of tables and graphs. The results of the study identified 33 types of medicinal plants that are often used by the people of Balla Disctrict. Keywords; mamasa, traditional medicine, forest plants.